Analisis Frekuensi Kerusakan Komponen Kontainer di PT X - Erica Geovany Sugianto; Felecia Felecia (Jurnal Titra, 2021)
PT X is a company focusing on shipping lines based in Surabaya. There is a high number of containers damaged which can reach 6.003% of the total assets or equivalent to 65,229 TEUs of containers (11 July 2020). This research aims to analyze container components that are frequently damaged, determine the cause of the damages, and provide prevention method in the form of work instructions. The implementation of this research follows the DMAIC method and used several quality tools to analyze it. The results showed that ten container components were frequently damage: panels, floorboards, gasket assembly, locking bar rods, cross members, gasket retainers strips, cam locking bars, hinge blades, serial number marking and locking bar handles. The causes of the component damage that often occur are incorrect handling at terminals and depots, and wrong processes for the stuffing and stripping. Prevention will minimize the occurrence of container component damage by creating work instructions for the stuffing and stripping process and cargo handling guidance for relations.